The prevalence of dental anomalies among Saudi Population in Makkah, Saudi Arabia - Dalal T. Mahjoub; Rahaf K. Jarwan; Lana A.Z. Filimban; Jumanah K. Bahatheq; Fayyad S. Alsharif; Omar Abdullah M. Alsharif; Salem H. Albalawi; Ahmed E. Rawas; Rahaf S. Najjar (Journal of Orthodontic Science)
BACKGROUND: Morphological and structural abnormalities are common dental anomalies. Identifying DA and determining their prevalence can play an important role in reducing the risk of surgical intervention and improving occlusion, leading to successful dental treatments. Thus, this study aimed to determine the prevalence of DA using panoramic radiographs (OPG) in Makkah, Saudi Arabia according to gender. MATERIALS AND METHODS: A retrospective radiographic investigation was performed, and the digital OPG of 923 patients (age range, 8–27 years) were collected. Records were collected from patients admitted at a government hospital in Makkah between January 2020 and DA in terms of tooth shape (microdontia, macrodontia, gemination, and fusion), number (supernumerary and congenitally missing teeth), and position (impaction and ectopic eruption). Several other abnormalities, such as ankyloses, dens in dents, dilacerations, and taurodontism, have also been reported. Digital radiographs from patients were systematically evaluated to diagnose each radiograph with consistent screen brightness and resolution. RESULTS: The most prevalent DA were impaction (53.8%), hypodontia (13.6%), microdontia (8.2%), and ectopic eruption (6.7%). Taurodontism was observed more frequently in male compared to female (7.5% and 2.2%, respectively). However, there was no significant difference between gender in the distribution of other DA. CONCLUSION: This study found that 27.8% of the Saudi population of Makkah city have DA. Clinical examination and radiographic evaluation are crucial for providing the proper treatment for patients seeking dental treatment.